Neural network and adaptive control for two-link planar manipulator - Nguyen, Vinh Quan (Journal of Technical Education Science, 2011)
The intelligent control systems, which are modeled after biological systems and human cognitive capabilities, possess learning, adaptation, and classification capabilities. As a result, these so-called intelligent controllers provide the hope of improved performance for today’s complex systems. These intelligent controllers were being developed using artificial neural networks (NN). In the paper, I explore a controller design using NN for Robotic since NN capture the parallel processing, adaptive, and learning capabilities of biological nervous systems